Clustering of social representations of tourists from different countries by the hospitality industry employees - Klimovich, Darya V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Social representations of tourists from different countries visiting the Republic of Belarus were studied from the point of view of hospitality industry employees. The method of semantic differential by 21 personal characteristics was applied. As a result of cluster analysis, 6 clusters were identified. The first cluster included representatives from Russia, Ukraine and Italy. The second cluster was formed exclusively by representatives of Belarus. The third cluster was formed by representatives from China, Israel and Turkey. The fourth cluster included representatives from the United Kingdom of Great Britain and Northern Ireland, Switzerland and Germany. The fifth cluster was formed by representatives of the United States, France and Poland, and the sixth cluster included representatives of Lithuania, Latvia and Estonia. Were identified and described differences between clusters.
Keywords: social representations; semantic differential; hotel business; hospitality industry; foreign tourists